Derivational Suffixes Analysis Found in “Every Summer After” Novel by Carley Fortune - I Gusti Ayu Arina Dwigiyanthi; Ida Bagus Gde Nova Winarta (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2024)
This study specifically concentrated on conducting an in-depth analysis of the various types of derivational suffixes. Derivational affixes were one of the most interesting topics to analyze, as they influence the formation of words from simple to complex ones. The data used in this analysis was sourced from the novel